Electrochemical characteristic of Biotinyl Somatostatin- 14/Nafion modified gold electrode in development of sensor for determination of Hg(II) - Daud, Nurulhaidah; Yusof, Nor Azah; Mohd Nor, Siti Mariam (Electrochemical Science Group, 2013)
Electrochemical sensor for Hg(II) has been developed using Biotinyl Somatostatin-14 peptide modified gold electrode utilizing nafion as the immobilizing agent. Experimental conditions such as pH, supporting electrolyte and scan rate were optimized. Detection of mercury using Biotinyl Somatostatin-14 peptide/Nafion has been observed to be optimum under acidic conditions. Good relative standard deviation of 3.7% has been obtained indicating reliability of the detection system. A linear calibration plot in the range of 40-170 µgL-1 was obtained with sensitivity value of 1×10-10 AµM-1. Limit of detection (LOD) obtained is 0.4 µgL-1 which is below the WHO guidelines for drinking water. The scan rate study showed that the process is a complex surface process, mostly involving an adsorption process. This developed method was applied for determination of Hg(II) in actual waste water samples and a good agreement was obtained between the proposed method and ICP-MS based on the analysis of the waste water samples.